N coupling with S-coordinated Ru nanoclusters for highly efficient hydrogen evolution in alkaline media. Issue 21 (23rd May 2021) - Li, Cheng-Fei; Zhao, Jia-Wei; Xie, Ling-Jie; Wang, Yu; Tang, Hai-Bo; Zheng, Li-Rong; Li, Gao-Ren
Abstract : Optimizing the coordination/surrounding environments of active metal nanoclusters to promote the catalytic performance during hydrogen evolution reaction (HER) in alkaline media is highly important but extremely challenging. Abstract : Optimizing the coordination/surrounding environments of active metal nanoclusters to promote the catalytic performance during hydrogen evolution reaction (HER) in alkaline media is highly important but extremely challenging. Here, we demonstrate that novel S-coordinated ruthenium (Ru) nanoclusters anchored on N/S-codoped carbon nanosheets (Ru–S/N–C) can be successfully synthesized via the space-confinement pyrolysis of Ru complexes in the framework of polyaniline–ammonia persulfate supermolecules. X-ray absorption fine structure spectroscopy and X-ray photoelectron spectroscopy studies reveal the local coordination structure of Ru–S bonds, the surrounding N/S/C environments of Ru, and the synergistic electronic interactions among N, S, C and Ru atoms. Theoretical calculations further confirm that the coordination/surrounding environments could optimize the adsorption energies of intermediates on Ru through interfacial charge transfer and, thus, accelerate the reaction kinetics of hydrogen evolution. The fabricated Ru–S/N–C exhibits an ultra-small overpotential of 10 mV at 10 mA cm −2 and an extremely high turnover frequency (TOF) of 2.3 H2 s −1 at an overpotential of 50 mV for the HER, as well as a mass catalytic activity about 10 times higher than that of a commercial Pt/C catalyst.